New chairperson of the committee on national issues and concerns - Office of the Chancellor - De La Salle University, Manila (Animo Repository, 2021)
After a process of consultation, Br. Bernie Oca pleased to announce the appointment of Dr. Jazmin Llana, Full Professor of the Department of Literature and former Dean of the College of Liberal Arts, as the new Chairperson of the Committee on National Issues and Concerns (CONIC) effective this Academic Year 2021-2022.